2017
DOI: 10.1097/tp.0000000000001273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Mobile Web App on Kidney Transplant Candidates' Knowledge About Increased Risk Donor Kidneys

Abstract: Background Kidney transplant candidates (KTCs) must provide informed consent to accept kidneys from increased risk donors (IRD), but poorly understand them. We conducted a multisite, randomized controlled trial to evaluate the efficacy of a mobile web application, Inform Me, for increasing knowledge about IRDs. Methods KTCs undergoing transplant evaluation at 2 transplant centers were randomized to use Inform Me after routine transplant education (intervention) or routine transplant education alone (control)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 43 publications
1
64
0
Order By: Relevance
“…In a study evaluating the ef-ficacy of a mobile web application for increasing knowledge about increased risk donor kidneys, intervention participants using the app had higher knowledge scores (mean difference: 6.61; 95% CI: 5.37–7.86) than control participants where the knowledge scale ranged from 0 to 31. 34 In another, patients who received intensive education about living donor transplant had higher knowledge (scaled from 0 to than patients who received usual care (12.7 vs. 11.7; P = .0008) one week after evaluation. 35 A systematic review concluded that decision aids were effective in improving treatment option knowledge and clearer expectations of treatment risks and benefits.…”
Section: Discussionmentioning
confidence: 92%
“…In a study evaluating the ef-ficacy of a mobile web application for increasing knowledge about increased risk donor kidneys, intervention participants using the app had higher knowledge scores (mean difference: 6.61; 95% CI: 5.37–7.86) than control participants where the knowledge scale ranged from 0 to 31. 34 In another, patients who received intensive education about living donor transplant had higher knowledge (scaled from 0 to than patients who received usual care (12.7 vs. 11.7; P = .0008) one week after evaluation. 35 A systematic review concluded that decision aids were effective in improving treatment option knowledge and clearer expectations of treatment risks and benefits.…”
Section: Discussionmentioning
confidence: 92%
“…This may reflect either the construction of the survey question, which asked if the recipient would "try to get a PHS high risk donor" or the need to improve the MTC presentation itself. The MTC's failure to encourage acceptance of increased risk deceased donor kidneys mirrors that of another mobile app-based decision-aid, the Inform Me app, which also seeks to increase ESRD patients' knowledge of the risks and benefits of increased risk deceased donor kidney options [30]. Using a randomized controlled trial design, a recently published evaluation of "Inform Me" found that while it was associated with a 44% higher increased risk kidney knowledge score than a control group, but was actually associated with a trend toward lower willingness to accept increased risk kidneys.…”
Section: Accepted Articlementioning
confidence: 99%
“…A previous study in liver transplant candidates and recipients showed that more than half the patients preferred being informed about donor‐related risks at the time of organ offer . Interventions such as decision aids and mobile apps have also been studied to assist patients in making decisions regarding transplant quality and appear to increase knowledge . The theoretical acceptance response collected via a survey in some of the quoted studies may be different than the actual acceptance response at the time of offer.…”
Section: Discussionmentioning
confidence: 99%